Locomotives of Local Growth: The Short- and Long-Term Impact of Railroads in Sweden - Thor Berger; Kerstin Enflo (European Historical Economics Society (EHES), 2013)
This paper uses city-level data to examine the impact of a first wave of railroad construction in Sweden, between 1855 and 1870, from the 19th century until today. We estimate that railroads accounted for 50% of urban growth, 1855-1870. In cities with access to the railroad network, property values were higher, manufacturing employment increased, establishments were larger, and more information was distributed through local post offices. Today, cities with early access to the network are 62% larger and to be found 11 steps higher in the urban hierarchy, compared to initially similar cities. We hypothesize that railroads set in motion a path dependent process that shapes the economic geography of Sweden today.
Keywords: N73; N93; R12; R40; 330; Railroads; Industrialization; Urban Growth; Path Dependence